(untitled) (Journal of EAHIL, 2017)
I was delighted to attend to 14th European Association Health Information Libraries Conference in Rome. It was a great opportunity for exposure to current best practices in the field of medical libraries and librarianship. Three days of the conference were launched with a keynote speech entitled “The open paradigm and the knowledge society recomposing the fragmentation: The role of the librarians” which was delivered by Maria Cassella. The speech emphasized the transformation of information, importance of digitization and “openness”. From the beginning to the end I have witnessed significant content and contributions to the conference by both participants and presenters. During the conference I acquired knowledge which will help to enrich my professional development as a medical librarian. The flow of the conference from general topics to each specific initiative, from challenging projects to hands on experiences allowed me to gain a considerable overview of health and medical libraries. From attending the conference I gained deeper understanding of my profession and I feel more confident and comfortable in day to day duties. The conference also afforded me an opportunity to network with valuable medical library professionals and practitioners. EAHIL has created a platform for me to observe and update myself on the on-going projects in different medical libraries around Europe! I am looking forward to attending to future EAHIL conferences and workshops.